Is the ‘Protected Designation of Origin’ an indicator for sustainable landscape management? Insights from pasture-based animal husbandry in five EU countries - Lukas Flinzberger; Tobias Plieninger; Miguel Nuno Bugalho; Yves Zinngrebe (Journal of Land Use Science)
Previous research has shown that products labeled as ‘Protected Designation of Origin’ (PDO) correlate positively with indicators for landscape sustainability. However, specific factors that turn PDO products into sustainable landscape management tools remain vague. We analyze interviews from six European production systems to explore the links between PDO-labeled products and sustainable landscape management. All case studies were linked to extensive animal husbandry. We found that PDO products can contribute to sustainable landscape management if well-adapted incentives for agri-environmental measures supplement income. Successful products are further associated with local networks that use synergies between different stakeholder interests. Due to their promotion of social-ecological goals at the landscape level, PDO products can be a powerful addition to the EU’s Green Deal and rural development strategy, and by introducing eligibility criteria that focus on social-ecological goals, PDO labeling could be classified as a sustainability standard.